(Invited) Nanostructured Silicon with Incorporated Bi-Metallic Nanostructures. (8th September 2020) - Rumpf, Klemens; Granitzer, Petra; Gonzalez-Rodriguez, Roberto; Coffer, Jeffery; Reissner, Michael
Abstract : Silicon nanotubes (SiNTs) and porous silicon (PSi) with comparable morphologies (inner tube diameter, pore diameter) are used as template materials for filling with magnetic bi-metal nanostructures. The nanostructures are grown chemically within these two template systems. In the case of NiCo, Co particles are grown chemically within the SiNTs and PSi whereas the Ni is deposited electrochemically afterwards. FePt particles are grown within both kind of structures from a H2 PtCl6 /Fe(NO3 )3 solution with varying Fe content. The magnetic response, especially with respect to the coercivity of all these different systems is investigated. The different metals (NiCo and FePt) offer drastic differences in their magnetic properties for both, porous silicon and silicon nanotubes. In all cases the metal loaded PSi offers higher coercivities compared to the SiNTs which should be due to less magnetic cross talk between the metal deposits.